Knowledge, attitudes and practices for the prevention of diabetic foot - Natalia de Sá Policarpo; Jayne Ramos Araujo Moura; Eugênio Barbosa de Melo Júnior; Paulo César de Almeida; Suyanne Freire de Macêdo; Ana Roberta Vilarouca da Silva
The purpose of this study was to identify the knowledge, attitudes and practices for the prevention of diabetic foot in patients with diabetes mellitus type 2. This study was based on a cross-sectional survey conducted in two Family Health Units, in the city of Picos - PI, Brazil, with 85 diabetics of both sexes, by means of a semi-structured Knowledge, Attitude and Practice questionnaire. There was a predominance of females in the study (62.4%). On the topic of foot care, 49.4% had no knowledge on hygiene or what to observe in their feet. In relation to nail care, 56.5% were unaware of the correct way to cut nails. Regarding attitudes, 80% were willing to engage in self-care. In terms of practice, results showed that activities such as washing, drying, moisturizing and massaging were not executed together. It is therefore necessary to develop educational strategies to create awareness, both for diabetics and health professionals, on the effective prevention of diabetic foot.